2016
DOI: 10.1002/mrm.26336
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of articular cartilage at 3T correlates with histology and biomechanics in a mechanical injury model

Abstract: DTI is sensitive in tracking early changes after mechanical injury, and its changes correlate with changes in biomechanics and histology. Magn Reson Med 78:69-78, 2017. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This experimental remodeling in goats was found to be consistent with the direction and magnitude of cartilage strain resulting collagen network remodeling from the orientation angles of ~85° in non-operated controls closer to 45° orientation angle in repaired tissue near the bonecartilage interface, and below and next to the defect (repair area). Moreover, diffusion tensor MRI based measurements in injured cartilage have shown a decrease of fractional anisotropy (Ferizi et al 2016) that can be related to the more disorganized collagen architecture, i.e., reorientation closer to the 45° orientation angles in the current model. Yet, it is not certain whether this experimentally observed decrease in the fractional anisotropy results from either disorganization/reorientation of collagen network or loss of proteoglycans or both.…”
Section: Comparison To Literaturementioning
confidence: 68%
See 1 more Smart Citation
“…This experimental remodeling in goats was found to be consistent with the direction and magnitude of cartilage strain resulting collagen network remodeling from the orientation angles of ~85° in non-operated controls closer to 45° orientation angle in repaired tissue near the bonecartilage interface, and below and next to the defect (repair area). Moreover, diffusion tensor MRI based measurements in injured cartilage have shown a decrease of fractional anisotropy (Ferizi et al 2016) that can be related to the more disorganized collagen architecture, i.e., reorientation closer to the 45° orientation angles in the current model. Yet, it is not certain whether this experimentally observed decrease in the fractional anisotropy results from either disorganization/reorientation of collagen network or loss of proteoglycans or both.…”
Section: Comparison To Literaturementioning
confidence: 68%
“…Injurious loading of cartilage can induce physical lesions in cartilage (Rolauffs et al 2010;Alexander et al 2012;Virén et al 2012;Myller et al 2016;Ferizi et al 2016). It has been suggested that the damage and disorganization of the collagen network could progress following an injury which may further accelerate cartilage degradation (Ferizi et al 2016). However, it is not known which mechanical signals of cartilage tissue change around a focal cartilage defect that could affect collagen disorganization and possible progression of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Roya et al reported that these scalar metrics detect early cartilage damage and are useful in diagnosis of osteoarthritis . These metrics are sensitive in tracking early changes after mechanical injury, and the changes that correlate with variations in biomechanics and histology …”
Section: Discussionmentioning
confidence: 99%
“…The proposed magic angle directional imaging represents an alternative method to the DTI, which is a widely used technique for fiber tractography. The present study did not involve a direct comparison with DTI, although it would be useful to perform such an investigation in the future.…”
Section: Discussionmentioning
confidence: 99%